2016
DOI: 10.1038/srep24236
|View full text |Cite
|
Sign up to set email alerts
|

Transcriptome Variability in Keratocystic Odontogenic Tumor Suggests Distinct Molecular Subtypes

Abstract: Keratocystic Odontogenic Tumor (KCOT) is a locally aggressive developmental cystic neoplasm thought to arise from the odontogenic epithelium. A high recurrence rate of up to 30% has been found following conservative treatment. Aggressive tumor resection can lead to the need for extensive reconstructive surgery, resulting in significant morbidity and impacting quality of life. Most research has focused on candidate-genes with a handful of studies employing whole transcriptome approaches. There is also the quest… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0
12

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(22 citation statements)
references
References 32 publications
1
9
0
12
Order By: Relevance
“…Based on their results, the authors confirmed that ameloblastomas and OKCs are distinct lesions, and according to the gene expression profile of ameloblastomas, these lesions are more similar to the dental lamina, while gene expression in OKCs indicates differentiation toward keratinocytes . Recently, microdissected OKC epithelial tissue from 20 sporadic cases was included in transcriptome analysis via whole‐genome microarray . The authors reported that PTCH1 and GLI were downregulated.…”
Section: Genetic Alterationsmentioning
confidence: 84%
See 1 more Smart Citation
“…Based on their results, the authors confirmed that ameloblastomas and OKCs are distinct lesions, and according to the gene expression profile of ameloblastomas, these lesions are more similar to the dental lamina, while gene expression in OKCs indicates differentiation toward keratinocytes . Recently, microdissected OKC epithelial tissue from 20 sporadic cases was included in transcriptome analysis via whole‐genome microarray . The authors reported that PTCH1 and GLI were downregulated.…”
Section: Genetic Alterationsmentioning
confidence: 84%
“…30 Recently, microdissected OKC epithelial tissue from 20 sporadic cases was included in transcriptome analysis via whole-genome microarray. 31 The authors reported that PTCH1 and GLI were downregulated. This last finding is in contrast with previous studies that used OKCs, medulloblastomas and skin tumors, which showed PTCH1 loss and GLI1 overexpression instead of downregulation.…”
Section: Global Molecular Alterationsmentioning
confidence: 99%
“…Quanto a análise comparativa direta entre os cimentos AH Plus e Sealer Plus, que possuem composição química semelhante, o resultado dos testes apresentou que o AH Plus possui diâmetro médio de escoamento maior do que o Sealer Plus, como corrobora o estudo realizado por Vertuan et al (2016).…”
Section: Metodologiaunclassified
“…Hu et al () compared the transcriptome of KCOT utilizing whole‐genome microarray with the ‘dentome’ and identified two different molecular subtypes operative in non‐syndromic KCOTs. In one molecular subtype, the phosphoinositide 3‐kinase/AK strain transforming (PI3K/AKT) pathway was functional, and in the other, mitogen‐activated protein kinase (MAPK) pathway was active.…”
Section: Lcm For Integrated Oral Biosciencesmentioning
confidence: 99%
“…The former has a gene expression profile similar to secretory ameloblast (s‐KCOT), while the latter had a gene expression profile resembling odontoblast (o‐KCOT). The common downregulated genes in these distinct molecular subtypes were PCTH‐1 and GLI‐1 (Hu et al , ). The authors concluded that even though the phenotype was same (both were KCOT), yet their response to therapy may be different (based on molecular pathway operative, i.e., their genotypes were different).…”
Section: Lcm For Integrated Oral Biosciencesmentioning
confidence: 99%